The diameter of the reachability set for a 2-D continuous-discrete linear system with disturbances - Krasoń, Ewa (Zielona Góra: Uniwersytet Zielonogórski)
The methods are presented for computing the support functions and diameters of reachability sets for a certain type of 2-D continuous-discrete linear system with disturbances limited to a rectangle and an ellipsoid. These methods are based on the idea of the reachability set for 1-D systems with disturbances and the 2-D continuous-discrete linear system theory.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka